PERAN GURU DAN ORANG TUA MEMBENTUK KARAKTER JUJUR PADA ANAK - Rochmawati, Nikmah (Universitas Islam Sultan Agung, 2018)
This paper is motivated by there are some dishonesty in the community, such as hoax news, hate speech, prejudice, cheating, corruption, theft, fraud, robbery that cause anxiety, mutual suspicion and disharmony in social life. Why does this happen? Because teachers at school and parents at home can not build honest characters to their children. Therefore, this writing will describe how teachers and parents form an honest character in children. Stages of character formation will be correlated with psychological theory. The results of the study found that to educate an honest character, children are not only given cognitive knowledge about honesty, but also must touch the level of affection domain and implemented in real behavior.